Analisis Regresi Data Panel: Operating Capacity, Profitability, Sales Growth, dan Capital Structure terhadap Financial Distress pada Perusahaan Subsektor Perdagangan Ritel - Erna Dwi Setyawati; R. Muh Syah Arief Atmaja Wijaya (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to examine and analyze the effect of operating capacity, profitability, sales growth, and capital structure on financial distress in retail trade subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employed a quantitative approach using secondary data obtained from the companies’ financial statements. The sampling technique applied was purposive sampling, resulting in 21 companies observed over a five-year period. Data analysis was conducted to determine the simultaneous and partial effects of the independent variables on financial distress. The findings indicate that operating capacity, profitability, sales growth, and capital structure simultaneously have a significant effect on financial distress. Partially, operating capacity, proxied by total asset turnover, and sales growth do not have a significant effect on financial distress. In contrast, capital structure, proxied by the debt-to-equity ratio, has a positive and significant effect on financial distress, while profitability, proxied by return on assets, has a negative and significant effect on financial distress. These findings suggest that capital structure and profitability are the primary determinants of financial distress in retail companies. Therefore, companies should maintain profitability and optimize capital structure management to minimize the risk of financial distress and enhance long-term financial performance.